2014
DOI: 10.1111/1751-2980.12199
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthy dietary behavior in refractory functional dyspepsia: A multicenter prospective investigation in China

Abstract: Unhealthy dietary behaviors, especially skipping meals, eating extra meals and a preference to sweet food and gas-producing food, were correlated with RFD and its subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
1
18
0
1
Order By: Relevance
“…Assisted population survey FD/IBS versus control subjects have fewer daily servings of fruit and vegetables, 0.82 versus 0.91 (P < 0.01), 2.51 versus 2.70 (P < 0.001), respectively Jiang (2014) 22 China FD versus control (n = 1414) Outpatient survey Differences between FD versus control 1. FD subjects have more erratic dietary habits (skipping meals [14.8% vs. 4.0], late meals [23.4% vs. 6.0%], and more snacking in between meals[14.1% vs. 3.0%]) than controls (P < 0.05) 2.…”
Section: Internet Population Surveymentioning
confidence: 99%
“…Assisted population survey FD/IBS versus control subjects have fewer daily servings of fruit and vegetables, 0.82 versus 0.91 (P < 0.01), 2.51 versus 2.70 (P < 0.001), respectively Jiang (2014) 22 China FD versus control (n = 1414) Outpatient survey Differences between FD versus control 1. FD subjects have more erratic dietary habits (skipping meals [14.8% vs. 4.0], late meals [23.4% vs. 6.0%], and more snacking in between meals[14.1% vs. 3.0%]) than controls (P < 0.05) 2.…”
Section: Internet Population Surveymentioning
confidence: 99%
“…Compared with nonspecific FD, significant differences in the frequency of meal skipping and fast intake have been reported by patients with dismotility-like FD and ulcer-like FD[ 2 ]. A large-sample multicenter study in China found that refractory FD patients often have unhealthy eating habits such as skipping meals, eating extra meals, or a preference for sweet food and gas-producing food[ 9 ].…”
Section: Behavioral Factors and Digestive Diseasesmentioning
confidence: 99%
“…According to the statistics, the prevalence of FD is as high as 20–30% [ 1 , 2 ]. The underlying pathogenesis includes diverse mechanisms, such as infectious causes represented by Helicobacter pylori ( H. pylori ) [ 1 – 6 ], diet factor [ 1 , 7 , 8 ], gastric acid [ 1 , 9 , 10 ], delayed gastric emptying, impaired proximal gastric accommodation [ 1 , 11 13 ], visceral hypersensitivity [ 1 , 14 16 ], duodenal inflammation [ 1 , 17 , 18 ], genetic factors [ 19 , 20 ], and psychosocial factors (such as anxiety, depression, and stress) [ 19 25 ]. Moreover, these factors may interact with each other under the participation of brain-gut axis [ 1 , 3 , 15 ].…”
Section: Introductionmentioning
confidence: 99%